Expectant Management of Miscarriage in View of NICE Guideline 154 - Junaid Rafi; Haroona Khalil (Hindawi Limited, 2014)
Objective. To find out the success rate of conservative management of complete two weeks for miscarriage in view of NICE Guideline 154. Design. Prospective observational study. Setting. Early pregnancy assessment units of District General Hospital in the United Kingdom. Participants. Women of less than 14 weeks' gestation, with a diagnosis of miscarriage (missed miscarriage/anembryonic or incomplete miscarriage). Interventions. Expectant management for two weeks. Main Outcome Measure. (1) Efficacy of 2-week expectant management, that is, complete resolution of miscarriage based either on self-reporting of patient after passing products of conception at home between D0 and D14 of expectant management or confirmation on scan at D14, and (2) short-term complications needing strong analgesia, blood transfusion, and antibiotics. Results. Expectant management of miscarriage for 2 weeks from the day of diagnosis was successful in 58% (64 /111) and failed in 42% (47/111). Conclusions. Expectant management success rate is consistent with the results from the longitudinal studies and RCTs published in the past. It is a safe option as none of the patients on expectant/medical management needed strong analgesia/antibiotics or blood transfusion.